Pedagogical culture development of the teacher of the future: scientific and practical point of view - Lyubov’ A. Kochemasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The need for scientific understanding and rethinking of modern problems in the theory and practice of education, as well as their adequate understanding and search for their effective solutions cannot be achieved without turning to the pedagogical heritage of the American pragmatist philosopher, sociologist and political scientist, psychologist and teacher, outstanding scientist and public figure John Dewey. In 1988, UNESCO recognized him as one of the four people who defined the way of pedagogical thinking in the twentieth century. Based on the above, the goal of the study is to create an attractive and open environment for current philosophical discussion, its cultural codes and scientific rethinking of the pedagogical heritage of D. Dewey. The author of the paper focuses on the pedagogical support of the teacher of the future in the field of popularization of science, which became possible due to the organization and holding of the International Competition of Scientific Research and Creative Works of Students “In the World of the Wise Thoughts of Nikolai Aleksandrovich Berdyaev and John Dewey.” In the study, the author’s attention is focused on the key idea of John Dewey in the development of the pedagogical culture of the teacher of the future, from which all his pedagogical principles stemmed. The applied value of the conducted research is determined by the expansion of the range of scientific and professional knowledge, the field of scientific knowledge, comprehension, and free choice of “personal research action” within the framework of updating the ideas of John Dewey. In modern pedagogical science and practice, the presented results of scientific research can be used as a tool for attracting educational subjects to the field of popularization of science.